Tuberculosis: the sanatorium season in the early 20th century - Patriarca, Carlo; Lo Bello, Giuseppe; Zannella, Stefano; Agati, Sergio Arturo (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
The creation of hospitals providing specialist care is not a prerogative of our time. As the world wonders how to cope with new pandemics and the age-old problems of the transmission of infections and the isolation of the sick, while the COVID-19 pandemic has been raging, it might be worth glancing back at the period – just over a century ago – when sanatoriums were set up in Italy as part of the fight against consumption.